Effect of multimodal physical exercise on sarcopenia parameters, dynamic balance, strength, and endurance in older healthcare professionals - Jiménez-Arellanes, Gabriel (2026)
Introduction: The aging process involves various conditions affecting the body, leading to a progressive decline in physical abilities. Objective: To determine the effect of a multimodal physical exercise program on sarcopenia parameters, dynamic balance, strength, and endurance in older adults. Methodology: A pre-experimental study was conducted with nine individuals aged 60 to 79 years, active healthcare professionals working in a public hospital for state workers in Baja California, Mexico. Sarcopenia was assessed using the SARC-F, while dynamic balance, strength, and endurance were evaluated using the Senior Fitness Test battery. A multimodal physical exercise program was implemented consisting of three sessions per week, 40 minutes per session, for 10 weeks. The exercises were organized in circuits that included three strength exercises, one endurance exercise, and one dynamic balance exercise per session. Results: The mean initial SARC-F score was 4.7 ± 0.6, and post-intervention it was 2.5 ± 0.5 (p=0.01). The mean initial strength was 10.5 ± 1.2 repetitions, and post-intervention it was 14.2 ± 2.0 (p=0.01). Although dynamic balance and endurance showed improved post-intervention scores, these were not statistically significant. Conclusion: Multimodal physical exercise significantly reduced SARC-F scores indicating sarcopenia and increased lower limb strength, suggesting that in this population, it represents a non-pharmacological strategy that supports prevention and treatment.